Model Business Agility pada Startup Digital: Studi pada Wirausaha Muda di Makassar - Nasir Pole . (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2026)
This study aims to explore and describe the business agility model in digital startups managed by young entrepreneurs in Makassar City. In a dynamic and uncertain digital business environment, adaptive capability becomes a key factor for business sustainability. This research employs a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving young entrepreneurs who manage digital startups. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings reveal that the business agility model is formed through four main dimensions: responsiveness, flexibility, speed, and innovation capability. These dimensions are integrated in shaping startups’ adaptive capacity to respond to market changes, adjust business strategies, make rapid decisions, and implement continuous innovation. The findings reinforce the perspectives of Dynamic Capability Theory and Resource-Based View, emphasizing adaptive capability as a source of competitive advantage. This study contributes conceptually by providing a contextual business agility model for regional digital startups and offers practical implications for strengthening the digital entrepreneurship ecosystem.